2017
DOI: 10.5114/ada.2017.69306
|View full text |Cite
|
Sign up to set email alerts
|

Dew drops on spider web appearance: a newly named pattern of IgG4 deposition in pemphigus with direct immunofluorescence

Abstract: Novel appearances in cutaneous pathology as well as mucocutaneous clinical signs are being described which indicate that this is still an attractive area for exploration. The H + E histology terms of “decorated tomb stoning” and “undecorated tomb stoning”, advocated by some pathologists, are misleading and as such should be avoided. Here, an appearance of IgG4 pemphigus deposits examined cost-effectively with direct immunofluorescence and suggested to be called “dew drops on spider web” is depicted in depth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Furthermore, the balance between SNPs involved in activating and inhibitory Fcγ receptor signaling may partially affect the development and progression of autoimmune diseases through the regulation of Th1 and Th2 cytokine levels. Our previous studies [5,28,29] demonstrated the role of IgG subclasses in a temporal analysis of humoral response in ABDs, indicating that CD16A polymorphisms (rs396991) are probably linked to the IgG1 subclass in pemphigus, and may therefore serve as a marker of chronic disease or remission.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the balance between SNPs involved in activating and inhibitory Fcγ receptor signaling may partially affect the development and progression of autoimmune diseases through the regulation of Th1 and Th2 cytokine levels. Our previous studies [5,28,29] demonstrated the role of IgG subclasses in a temporal analysis of humoral response in ABDs, indicating that CD16A polymorphisms (rs396991) are probably linked to the IgG1 subclass in pemphigus, and may therefore serve as a marker of chronic disease or remission.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, novel appearances in cutaneous pathology of autoimmune blistering diseases have been described using various microscopic systems (Dmochowski, Gornowicz‐Porowska, & Bowszyc‐Dmochowska, ). In light of this, a newly named pattern of IgG4 DIF deposition (“dew drops on spider web”) in pemphigus was proposed (Dmochowski et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, novel appearances in cutaneous pathology of autoimmune blistering diseases have been described using various microscopic systems (Dmochowski, Gornowicz‐Porowska, & Bowszyc‐Dmochowska, ). In light of this, a newly named pattern of IgG4 DIF deposition (“dew drops on spider web”) in pemphigus was proposed (Dmochowski et al, ). Excitingly, reflectance confocal microscopy has already been used for patterning of desquamative gingivitis seen in pemphigus vulgaris, mucous membrane pemphigoid and oral lichen planus in vivo (Alessi, Nico, Fernandes, & Lourenço, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, autoimmune process taking place in nail bed, matrix, and periungual nail fold could be explained by plausible complex associated with different expression of desmosomal cadherins in nail structures epithelia in comparison with skin and mucous membranes. Transitive stratified squamous epithelium could be regarded a target of immunization similarly as at other affected sites, what corresponds with acantholysis and PV patterns of IgG, IgG1, and IgG4 in DIF ( 21 ). Relative rarity of nail apparatus involvement is considered by some a consequence of partial sequestration of target antigens in proximal nail matrix (PNM) and reduced number of antigen presenting cells as well as depression of their functions in comparison to mucosal and skin immune system, but resembling the one of hair follicle ( 31 , 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…IIF study on monkey esophagus in PV reveals circulating IgG/IgG4 class of pemphigus-type autoantibodies against desmosomal proteins of keratinocytes. Classic DIF of perilesional skin/mucosa in PV shows “fishing-net”/“honeycomb”/“basket weave”/“chicken wire” pattern (intercellular IgG+/-C3 deposits) ( 20 ) and “dew drops on spider web” appearance (punctate/granular intercellular IgG4 deposits) ( 21 ). For low-invasive diagnosis—perilesional skin can be substituted with plucked hair ( 21 ).…”
Section: Introductionmentioning
confidence: 99%